Pemetaan dan Pengaruh Debit Banjir Terhadap Tata Guna Lahan Di Kelurahan Sekarjaya (Studi Kasus: RSS Sriwijaya) - Azwar, Azwar; Lucyana, Lucyana; Meiwinda, Eka Rizki; Rezaliyanti, Fety (UNIVED Press, 2024)
Rapid population growth and large amounts of land being converted into housing, especially in the Sekarjaya Village at Sriwijaya Hospital, with these changing conditions, make the Sriwijaya Hospital area prone to flooding when the rainy season arrives. Therefore, an analysis of the influence of flood discharge on changes in land use in Sekarjaya Village was carried out. The results of the flood discharge analysis for the 10 year period show that the increase in discharge in 2014 reached 14,863.81 m3/sec and in 2024 it reached 100,818.46 m3/sec. Based on the analysis, it can be concluded that changes in land use around the Sriwijaya RSS are related to the magnitude of flood discharge in the Sriwijaya RSS watershed.